Mandibular Reconstruction with a Free Rib Graft: Case Report and Literature Review - Silva, Kariny Oliveira; Lima, Diego Learth; Lopes Filho, Antônio Mont'Alverne; Menezes Júnior, José Maria Sampaio; Gondim, Ricardo Franklin; Thompson Gonçalves Filho, Raimundo; Teixeira Neto, Murilo Alves; Parente, José Lincoln Carvalho (Brazilian Journal of Case Reports, 2025)
The reconstruction of mandibular defects is essential to restore facial function and aesthetics in patients undergoing mandibular resections, a treatment indicated in approximately 41.8% of ameloblastoma cases. This study presents a secondary approach to partial mandibular reconstruction using a rib bone graft in the left mandibular body region of an adult female patient who underwent surgical resection of an ameloblastoma in 2019. Ten months postoperatively, the patient has shown reasonable maintenance of bone graft volume. The rib graft proved to be a viable surgical technique for mandibular reconstructions in centers lacking specialized teams for harvesting from other donor sites, as evidenced by this case and cited literature.